Completing the Journey: Scriptural Exegesis in Augustine's Confessions - Haflidson, Ronald (My University, 2007)
Saint Augustine's Confessions stands as one of the most widely read works of the Western tradition. Despite its popularity there remains a greatly contested question fundamental to understanding Confessions: how do all the books cohere? The question about coherence arises because the "autobiographical" books (1-IX) differ markedly from the "philosophical" ones (X-XIII). This division is evident in that many treatments of Confessions only consider the first nine books. It is the contention of this thesis that the final three books are absolutely essential to a complete reading of Confessions. In the final three books Augustine develops his understanding of creation, his ecc1esiology, his hermeneutics and his Trinitarian doctrine. This thesis seeks to show how the Scriptural exegesis of the final three books completes the journey of Confessions-the journey to rest in the Triune God-as described in the first ten books.
Keywords: Religion; Religion